Science Learning Model for Kindergarten - Denny Setiawan; Sri Tatminingsih (International Conference on Education and Language (ICEL), 2013)
Science education is essential to the development of kindergarten students. Integrating science education into education from an early age, intended to help children understand the world around them and improve critical thinking skills. Science can not be taught to children in a way like other knowledge that is to tell the children directly yield discoveries in science. This is because on the one hand, science is observation and exploration of the world around us, including questioning, investigating, analyzing, and drawing conclusions. On the other hand, children are often eager to know and they are intuitive. They try to understand the reasons why things happen and busy looking for answers. In other words, they seem to have a natural aptitude for science. Thus, children should be actively involved in the learning process of science. This research isthe development ofa modelthat aims to makescience learning strategy forkindergartenchildrentodeveloptheir potentialas a researcherin the future. The research beganwith capturing the habits, needs, and hopes ofkindergarten teachersin the teaching ofsciencethrough a questionnaire. The resultstogether withthe results ofliterature studyonthe teaching of science, usedto make a prototypeofsciencelearningmodel in kindergarten. Then theprototypewastestedin a limited areain somekindergartenstoget inputas a revisionmaterial. This guide wasthenrevisedand will bewidely disseminatedtootherkindergartens asan innovation inscience learningin kindergarten